Parental alcohol consumption and risk of leukemia in the offspring: a systematic review and meta-analysis. Issue 5 (September 2017) - Karalexi, Maria A.; Dessypris, Nick; Thomopoulos, Thomas P.; Ntouvelis, Evangelos; Kantzanou, Maria; Diamantaras, Andreas-Antonios; Moschovi, Maria; Baka, Margarita; Hatzipantelis, Emmanuel; Kourti, Maria; Polychronopoulou, Sophia; Stiakaki, Eftichia; et al.
Abstract : Parental alcohol consumption before and during pregnancy has been linked to adverse outcomes in the offspring including leukemogenesis. We, therefore, aimed to systematically assess and quantitatively synthesize published data on the association of paternal consumption during preconception and maternal consumption during pregnancy with leukemia risk in childhood (0–14 years). Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we searched PubMed (until February 2016) and the reference lists of the relevant studies. Observational studies examining the association between parental alcohol consumption and childhood leukemia were considered eligible. Data extracted from 39 case–control studies (over 16 000 leukemia cases and 30 000 controls) were pooled and summary-effect estimates were calculated. Subgroup analyses were carried out by main acute leukemia type [lymphoblastic or myeloid), cytogenetics/genetic polymorphisms, and specific alcohol beverages. We found a statistically significant dose–response association of any level of maternal alcohol consumption compared with nondrinking during pregnancy exclusively with acute myeloid leukemia (AML) [odds ratio (OR)moderate consumption : 1.64, 95% confidence intervals (CIs): 1.23–2.17 and ORhigh consumption : 2.36, 95% CI: 1.60–3.49]. In contrast, no association of paternal preconception consumption with any leukemia type was noted. In beverage-specific analyses, only a positive association of maternal wine drinking with childhood AML was found, which was more pronounced in analyses including only studies on infant leukemia (ORwine : 2.12, 95% CI: 1.16–3.90). The largest ever meta-analysis shows a sizeable, statistically significant dose–response association of maternal alcohol consumption during index pregnancy with AML risk. Future research exploring the role of genetic polymorphisms is anticipated to shed light on the underlying pathophysiology. Abstract : Supplemental Digital Content is available in the text.